Pilot study on neonicotinoids in Finnish waterbirds: no detectable concentrations in common goldeneye (Bucephala clangula) plasma - Ask, Amalie V.; Gómez-Ramírez, Pilar; Jaspers, Veerle L. B.; Fenoll, José; Cava, Juana; Vakili, Farshad S.; Lemesle, Prescillia; Eeva, Tapio; Davranche, Aurélie; Koivisto, Sanna; Hansen, Martin; Arzel, Céline (Springer Science and Business Media LLC, 2025)
Neonicotinoids have been detected in farmland-associated birds and exposure to these insecticides has been linked to adverse effects. Even though neonicotinoids are mobile and persistent and have been detected in surface waters and aquatic invertebrates, there is a considerable lack of knowledge on their occurrence in waterbirds. Here we investigated the occurrence of seven neonicotinoids and some of their transformation products (imidacloprid, thiacloprid, thiamethoxam, acetamiprid, clothianidin, dinotefuran, nitenpyram, 6-chloronicotinic acid, hydroxy-imidacloprid, imidacloprid-urea, imidacloprid-olefin, thiamethoxam-urea, thiacloprid-amide, acetamiprid-acetate, and acetamiprid-desmethyl) in blood plasma of 51 incubating female common goldeneyes (Bucephala clangula). We collected samples from five different regions from southern to northern Finland encompassing rural and urban settings in coastal and inland areas. Surprisingly, none of the targeted neonicotinoids was found above the limit of detection in any of the samples. As neonicotinoid concentrations in wild birds can be very low, a likely reason for the nil results is that the LODs were too high; this and other possible reasons for the lack of detection of neonicotinoids in the goldeneyes are discussed. Our results suggest that neonicotinoid exposure in their breeding areas is currently not of major concern to female goldeneyes in Finland. Even though this study did not find any immediate danger of neonicotinoids to goldeneyes, further studies including surface water, aquatic invertebrates, and other bird species could elucidate potential indirect food chain effects.